Determinación de los factores del consumo de alcohol en los estudiantes del Colegio Nacional Eloy Alfaro - Cañar Cuenca, Diego Vicente (2015)
In the field of health, there are many problems to investigate; however, there is a topical subject that complicates the setting of public health, due to the increase of the consumption of alcohol in a manner disproportionate in adults, and especially in teenagers, what deserves a commitment of the State, society and family, to deal with it, from its multi-faceted, this present research work called “DETERMINATION OF THE FACTORS OF THE CONSUMPTION OF ALCOHOL IN THE STUDENTS OF THE NACIONAL ELOY ALFARO SCHOOL” it is a descriptive study. Developed in the academic period April 2014 - February 2015. For the collection of the information, the survey was applied to 109 students of the third year of high school, with questions related to social and psychological factors determining the following results: 95% of students consumed alcohol and 63% do so sometimes; and, Between the social and psychological factors related to the consumption of alcohol are: familiar problems or of work with (50 %); and, the social commitments (41.28 %). In regard to the information received on the prevention of alcohol consumption on the part of the campus 72% report having received information about the topic. Keywords: Alcoholism, alcohol consumption, Teenagers